OPTIMASI PEMBELAJARAN DARING DAN PERAN METODE DEMONSTRASIDALAM PENINGKATAN HASIL BELAJAR PENDEKATAN BERBASIS PROYEK UNTUK MASA DEPAN PENDIDIKAN - Ganang Trinidad (CV. ADIBA AISHA AMIRA, 2024)
This research aims to analyze the effect of online learning in building engineering drawing subjects on students' conceptual understanding and practical skills. This research will evaluate the effectiveness of online learning in facilitating an in-depth understanding of the principles of building engineering drawing as well as students' ability to apply them practically. Apart from that, this research will also examine factors that influence the success of online learning, such as the level of interactivity, accessibility and quality of learning content.